Assessment of knowledge, attitudes, and practices regarding premarital genotype counselling and testing for sickle cell disease among African international students at universities in Gujarat state, India - Adamu, Ismaila (International Journal Of Community Medicine And Public Health, 2026)
Background: Sickle Cell Disease (SCD) is a common inherited blood disorder, especially in sub-Saharan Africa, where over 300,000 infants are born with SCD each year, with 75% of these cases occurring in Africa. This study aimed to evaluate the knowledge, attitudes, and practices regarding premarital genetic counselling and testing for SCD among African international students in Gujarat State, India. Methods: A cross-sectional descriptive design was adopted, involving a sample of 99 students who were selected through convenience sampling. Data were collected through questionnaires. Analysis was performed using IBM SPSS version 20. Results: Most respondents (92.9%) were aware of SCD, with 66.7% citing media (TV, radio, internet) as their source of information. About 69.6% recognized genetic mutation or inheritance as a cause. A significant majority (72.7%) agreed that SCD can be diagnosed through blood tests, and 78.8% believed that couples with AS genotypes should avoid marriage. However, 61.6% had not undergone genotype testing, and the same proportion lacked education or counselling about SCD. Conclusions: Although awareness of SCD is high, many participants do not know their genotype and have not received sufficient information or counselling regarding the disease.